1994
DOI: 10.1139/g94-081
|View full text |Cite
|
Sign up to set email alerts
|

Active maize genes are unmodified and flanked by diverse classes of modified, highly repetitive DNA

Abstract: We have characterized the copy number, organization, and genomic modification of DNA sequences within and flanking several maize genes. We found that highly repetitive DNA sequences were tightly linked to most of these genes. The highly repetitive sequences were not found within the coding regions but could be found within 6 kb either 3' or 5' to the structural genes. These highly repetitive regions were each composed of unique combinations of different short repetitive sequences. Highly repetitive DNA blocks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
128
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(137 citation statements)
references
References 47 publications
7
128
2
Order By: Relevance
“…Two different wash conditions, a low stringency ‫ן1(‬ SSC at 65°C) and a high stringency ‫ן1.0(‬ SSC at 65°C) were compared to determine how much of the difference in signal was attributable to sequence divergence (Table 5). Relative abundances of the different families are in fairly good accordance with the abundance estimates derived from Table 2, and with those described more generally in similar dot-blot experiments (Bennetzen et al 1994). The copy number of most of these elements doubles under low stringency hybridizations ‫ן1(‬ SSC; Table 5), possibly indicating the presence of extended and overlapping divergent families of retroelements and explaining at least partly the fact that estimates based on hybridization tend to be higher than those based on sequence analysis (Table 1).…”
Section: Maize Repetitive Elementssupporting
confidence: 88%
See 1 more Smart Citation
“…Two different wash conditions, a low stringency ‫ן1(‬ SSC at 65°C) and a high stringency ‫ן1.0(‬ SSC at 65°C) were compared to determine how much of the difference in signal was attributable to sequence divergence (Table 5). Relative abundances of the different families are in fairly good accordance with the abundance estimates derived from Table 2, and with those described more generally in similar dot-blot experiments (Bennetzen et al 1994). The copy number of most of these elements doubles under low stringency hybridizations ‫ן1(‬ SSC; Table 5), possibly indicating the presence of extended and overlapping divergent families of retroelements and explaining at least partly the fact that estimates based on hybridization tend to be higher than those based on sequence analysis (Table 1).…”
Section: Maize Repetitive Elementssupporting
confidence: 88%
“…Repetitive DNA in plants is often methylated, whereas single or low-copy sequences such as genes are usually hypomethylated (Bennetzen et al 1994). Rabinowicz et al (1999) demonstrated that many repeated DNA sequences in maize can be excluded from small-insert DNA libraries using bacterial restriction-modification systems to select against methylated DNA sequences.…”
Section: Hypomethylated Regions Contain Few Members Of Abundant Retromentioning
confidence: 99%
“…Seventeen clones carrying maize repetitive nucleotide sequences (30) were kindly provided by J. Bennetzen (Purdue University, West Lafayette, IN). A clone containing the maize 185-bp knob repeat (36) was provided by W. Peacock (Commonwealth Scientific and Industrial Research Organization, Canberra, Australia).…”
Section: Methodsmentioning
confidence: 99%
“…The success of isolating maize DNA from oat-maize chromosome-addition lines depends on how many maize-specific (relative to oat) high-copy-number dispersed nucleotide sequences are found in the maize genome. Genome analysis in grasses, including maize and oat, reveals that a major portion of genomic DNA consists of families of repetitive sequences dispersed throughout the genome (26,29,30). According to DNA-DNA renaturation data in maize (28), unique sequences of average length 2,100 bp are interspersed with mid-repetitive sequences.…”
mentioning
confidence: 99%
“…MF has already been applied successfully in maize (Zea mays), sorghum (Sorghum bicolor), and cowpea (Vigna unguiculata; Rabinowicz et al, 1999;Palmer et al, 2003;Whitelaw et al, 2003;Chen et al, 2007). The development of MF followed studies of genome architecture that revealed that repetitive elements tend to form clusters within plant genomes that become heavily methylated (hypermethylated), leaving stretches of less-methylated (hypomethylated), low-copy gene-rich space scattered in islands throughout the genome (Bennetzen et al, 1994;Bedell et al, 2005).…”
mentioning
confidence: 99%